Rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst and preparation method thereof
By combining zinc oxide with titanium dioxide and doping rare earth ytterbium and erbium ions, a rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst was solved, and printing and dyeing was achieved Efficient degradation and green treatment of wastewater.
Patent Information
- Application Number
- CN202411685990.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The band-blocking width of existing titanium dioxide photocatalysts limits their light response range, resulting in low photo quantum efficiency and making it difficult to effectively degrade dye pollutants in printing and dyeing wastewater.
By compounding zinc oxide with titanium dioxide and doping rare earth ytterbium and erbium ions, a rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst is formed to expand its photoresponse range and improve photocatalytic activity.
The specific surface area of the composite photocatalyst increases, and the energy band band barrier width decreases, which can effectively degrade methylene blue in the printing and dyeing wastewater, improve the wastewater treatment efficiency, and reduce the generation of secondary pollutants.
Smart Images

Figure CN119386850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sewage treatment, in particular to the preparation of titanium dioxide composite materials, and in particular to a preparation method of a rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst for photocatalytic degradation of methylene blue. Background Art
[0002] Acid rain, eutrophication of water bodies, black and smelly water bodies, excessive PM2.5 and other problems occur frequently, warning that environmental protection is urgent. The textile printing and dyeing industry consumes a lot of water, and the wastewater is complex, containing high concentrations of organic pollutants and pigments, which seriously affects the water quality of the region. At present, my country's printing and dyeing wastewater is mainly dyeing wastewater. According to the chemical structure, 80% of the dyes are insoluble in printing and dyeing wastewater. Water treatment researchers at home and abroad have conducted in-depth research on its treatment technology. At present, the treatment methods for printing and dyeing wastewater mainly include physical treatment, biochemical treatment and chemical treatment. Photocatalytic technology, as a new type of sewage treatment technology gradually developed on the basis of photochemical oxidation, has the advantages of good stability, high activity, non-toxicity, wide application range, and no secondary pollution. It can effectively degrade dye pollutants in water bodies, so it has received widespread attention from scholars.
[0003] In photocatalytic research, photocatalysts are mostly n-type semiconductor materials, such as TiO2, ZnO, CdS, etc. TiO2 is the most widely studied and applied n-type semiconductor material, with advantages such as high chemical stability, non-toxicity, low cost, strong photosensitivity, etc. TiO2 is used in photocatalytic reactions, such as water treatment, air purification, solar cell photosensitizer, self-cleaning materials and medical applications. The photocatalytic mechanism of TiO2 is shown in the figure below. Figure 1 As shown in the figure, when TiO2 is irradiated with ultraviolet light corresponding to the bandgap width, the valence band electrons absorb energy to generate excited electrons, forming holes in the valence band. The excited electrons react with oxygen in the air to generate superoxide radical anions, and the holes combine with water molecules to form hydroxyl radicals. The hydroxyl radicals and superoxide radicals with strong oxidizing properties react with the printing and dyeing wastewater and are then converted into harmless small molecules such as water and carbon dioxide.
[0004] However, due to the band gap of TiO2 being 3.0 to 3.2 eV, it can only be excited by ultraviolet light with a wavelength less than 387 nm, and the photogenerated electron pairs are very easy to recombine, resulting in a low photon efficiency, which is greatly limited in practical applications. In order to improve the photocatalytic performance of TiO2, people have studied a variety of modification methods, including precious metal deposition, transition metal doping, rare earth metal doping, titanium dioxide composite modification, etc., to optimize the structure of TiO2, thereby expanding its light response range and reducing the carrier recombination rate.
[0005] At present, there are two commonly used methods to solve the bandgap energy problem of titanium dioxide: 1. Rare earth metal doping will cause local changes in the structure of titanium dioxide, increasing oxygen vacancies and forming more capture centers. In addition, its upconversion luminescence performance can be used to convert visible light or infrared light in sunlight into ultraviolet light that can be used by TiO2, thereby improving the utilization rate of sunlight by photocatalysts. 2. Semiconductor recombination, combining two or more semiconductors together, can not only increase the absorption in the visible light region, but also reduce the recombination of carriers, thereby improving photocatalytic activity. Due to the semiconductors between the conduction bands of different energy levels, light-excited electrons can quickly move from one semiconductor to the adjacent semiconductor, thereby accelerating the separation of electron-hole pairs and improving photocatalytic activity. Summary of the invention
[0006] Semiconductor recombination can effectively increase the specific surface area of semiconductors, increase the absorption spectrum of semiconductors, and semiconductor recombination with different bandgap widths can effectively achieve the separation of electron-hole pairs; rare earth metal doping can form more oxygen vacancies, which can promote the effective separation of photogenerated electron-hole pairs. In addition, rare earth metal ions, due to their unique electronic orbital structure, will reduce the bandwidth of TiO2, thereby expanding its light response range from the ultraviolet and near-ultraviolet light regions to the visible light region. Since these two methods mainly improve the photocatalytic activity from different angles, combining the two methods can further improve the photocatalytic intensity of titanium dioxide. In summary, the present invention provides a method for preparing a new type of titanium dioxide material with higher photocatalytic activity and better degradation of printing and dyeing wastewater.
[0007] The present invention is achieved through the following technical solutions:
[0008] A rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst, zinc oxide and titanium dioxide are compounded to obtain a composite photocatalyst, and then rare earth Yb is doped 3+ and Er 3+ , rare earth Yb 3+ and Er 3+ The ratio of Zn to Ti needs to be configured; n(Zn):n(Ti)=5%, 10%, 15%, Er 3+ The doping ratio of Yb is fixed at n(Er):n(Ti)=1%, 2.5%, 5%; 3+ They are n(Yb):n(Ti)=1%, 2.5% and 5% respectively.
[0009] Furthermore, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%.
[0010] Furthermore, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1%.
[0011] Furthermore, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%.
[0012] Furthermore, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
[0013] Furthermore, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
[0014] The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
[0015] Furthermore, the preparation method of the rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst comprises the following steps:
[0016] (1) First, weigh 7 mL of tetrabutyl titanate and add it to 25 mL of anhydrous ethanol solution; and stir the mixed solution of the two by magnetic stirring;
[0017] (2) Accurately weigh a certain amount of ytterbium nitrate and erbium nitrate, put them into a beaker, add anhydrous ethanol and glacial acetic acid into a volumetric flask; stir the mixed solution magnetically;
[0018] (3) slowly adding the mixed solution (2) into the mixed solution (1), stirring with a magnetic stirrer until a transparent sol is obtained;
[0019] (4) standing at room temperature for aging, and then moving to a drying oven to dry into a xerogel;
[0020] (5) Grinding the dry gel, transferring it to a crucible, and placing it in a muffle furnace for calcination. When it cools to room temperature, taking out the product; washing the product by centrifugation (using deionized water and ethanol to wash the product respectively);
[0021] (6) Add an appropriate amount of zinc acetate to 10 mL of anhydrous ethanol and stir evenly;
[0022] (7) Take out an appropriate amount of the particles in (5), add them to (6), stir and soak, and then centrifuge;
[0023] (8) The solid powder obtained in (7) is dried, and then calcined in a muffle furnace. When the solid powder is cooled to room temperature, the product is taken out.
[0024] Furthermore, the YbN3O9·5H2O solution in step (2) is 0.1 mol / L, the Er(NO3)3·5H2O solution is 0.1 mol / L, and the C4H6O4Zn·2H2O solution in step (8) is 0.2 mol / L.
[0025] Furthermore, the magnetic stirring time in step (2) is 10 min;
[0026] The volumetric flask in step (3) has a size of 100 ml;
[0027] The magnetic stirring time in step (3) is 30 min;
[0028] The stirring time of step (5) is 30 min;
[0029] The drying oven temperature in step (7) should be set to 90°C for 6 hours;
[0030] The muffle furnace calcination temperature in step (8) is 500° C. and the calcination time is 2 h.
[0031] The improved effects of the present invention are as follows: when compounded with semiconductor ZnO, a heterojunction structure is formed, which promotes the effective separation and transmission of photogenerated electrons and holes, reduces the forbidden band width of the photocatalyst, and the doping of ytterbium ions and erbium ions can cause the light absorption band edge of TiO2 and ZnO to redshift, reduce the band gap, and broaden its visible light response range. The crystal particles obtained by doping with rare earth ions are very small, which will greatly increase the specific surface area of the TiO2 / ZnO composite photocatalyst, thereby enhancing the photocatalytic performance. Under the same illumination conditions, the composite photocatalyst may have a higher wastewater treatment efficiency than a single photocatalyst or an undoped photocatalyst, shorten the treatment time, and the photocatalytic process does not produce or produces very little secondary pollutants, which is helpful to achieve green treatment of printing and dyeing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The microstructure of the product obtained in Example 1 observed under a scanning electron microscope.
[0033] Figure 2 The microstructure of the product obtained in Example 2 observed under a scanning electron microscope.
[0034] Figure 3 This is the X-ray photoelectron spectroscopy analysis diagram of the product obtained in Example 2.
[0035] Figure 4 The microstructure of the product obtained in Example 3 observed under a transmission electron microscope.
[0036] Figure 5The microstructure of the product obtained in Example 4 observed under a transmission electron microscope.
[0037] Figure 6 The microstructure of the product obtained in Example 5 observed under a scanning electron microscope.
[0038] Figure 7 The X-ray diffractometer analysis diagram of the products obtained in Examples 1, 2 and 6.
[0039] Figure 8 The photocatalytic mechanism proposed for this new composite photocatalyst. DETAILED DESCRIPTION
[0040] Unless otherwise indicated, implied from the context, or customary in the prior art, the tests and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application, or publication referred to in this application are incorporated herein by reference in their entirety, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, products, and processing designs disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0041] Although traditional titanium dioxide materials are widely used in the photocatalytic treatment of printing and dyeing wastewater, the low utilization rate of solar energy and the high recombination rate of photogenerated holes and electrons also limit their large-scale use. Therefore, the research on semiconductor composite and rare earth doping of titanium dioxide has become an effective way to improve the photocatalytic activity of titanium dioxide, which has important value and significance for the actual market application of titanium dioxide photocatalytic materials. This method adopts the sol-gel method to prepare a new titanium dioxide composite material, with titanium dioxide as the substrate, composite zinc oxide semiconductor, and then doped with rare earth ytterbium and erbium ions. The prepared new material has a significant improvement in the degradation efficiency of printing and dyeing wastewater, such as methylene blue, compared with commercial titanium dioxide. This method is simple, convenient, and efficient, and can be promoted on a large scale for the photocatalytic degradation of printing and dyeing wastewater.
[0042] Example 1
[0043] A new type of titanium dioxide material is achieved through the following ways:
[0044] (1) First, take 7 mL of tetrabutyl titanate solution and add it into 25 mL of water-free ethanol. The mixed solution of the two is magnetically stirred.
[0045] (2) Accurately weigh a certain amount of ytterbium nitrate and erbium nitrate, put them into a beaker, add anhydrous ethanol and glacial acetic acid into a volumetric flask, and stir the mixed solution magnetically.
[0046] (3) The mixed solution obtained by stirring (2) is slowly added dropwise to the mixed solution obtained by stirring (1), and stirred using a magnetic stirrer until a transparent sol is obtained.
[0047] (4) Allow to stand at room temperature for aging, and then move to a drying oven to dry into a xerogel.
[0048] (5) Grind the dry gel and transfer it to a crucible and place it in a muffle furnace for calcination. When it cools to room temperature, take out the product and wash the product by centrifugation (wash the product with deionized water and ethanol respectively).
[0049] (6) Add an appropriate amount of zinc acetate to 10 mL of anhydrous ethanol and stir evenly.
[0050] (7) Take out an appropriate amount of the particles in (5), add it to (6), stir and soak, and then centrifuge.
[0051] (8) The solid powder obtained in (7) is dried, and then calcined in a muffle furnace. When the solid powder is cooled to room temperature, the product is taken out.
[0052] The molar ratio of Zn to Ti in the novel titanium dioxide material obtained in this embodiment is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, the prepared novel titanium dioxide photocatalytic material has a significant increase in the absorption capacity of long-wavelength light, which shows that the novel photocatalytic material has an enhanced absorption capacity for incident light compared with pure titanium dioxide, can stimulate more photogenerated carriers, thereby improving the photocatalytic degradation ability, and has a strong degradation effect on methylene blue solution.
[0053] Example 2
[0054] In the preparation process of the new titanium dioxide composite material according to claim 1, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1%. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope, X-ray photoelectron spectroscopy and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, the photocatalytic effect of the new titanium dioxide material is also better than that of pure titanium dioxide, with a rough surface and a large specific surface area. At the same time, after repeated experiments, the degradation efficiency of the methylene blue solution is above 95%, which shows that the photocatalytic stability of the new titanium dioxide material is relatively high.
[0055] Example 3
[0056] In the preparation process of the new titanium dioxide composite material according to claim 1, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, its photocatalytic effect is also better than pure titanium dioxide, but with the increase of Yb ions, the decrease of Er ions hinders the adsorption and reaction of reactant molecules, resulting in a decrease in photocatalytic efficiency.
[0057] Example 4
[0058] In the new titanium dioxide material obtained in this embodiment, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, the photocatalytic effect of the new titanium dioxide material is also better than that of pure titanium dioxide, but with the reduction of rare earth ion doping, the specific surface area is reduced, and the amplitude of the reduction of the energy band forbidden degree of the new material is reduced. The degree of reduction of the energy barrier of photogenerated electrons from the valence band to the conduction band is also reduced, which is not conducive to the conduction of photogenerated electrons. Therefore, the photocatalytic activity is reduced compared with Example 2.
[0059] Example 5
[0060] In the novel titanium dioxide material obtained in this embodiment, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1.5%. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, the average particle size of the novel titanium dioxide material in this ratio is not much different from that of pure nano titanium dioxide, which is not conducive to the occurrence of photocatalytic reaction, and the degree of improvement of photocatalytic activity is also relatively low.
[0061] Example 6
[0062] In the novel titanium dioxide material obtained in this embodiment, the molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, scanning electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by methylene blue solution under visible light, as the concentration of doped rare earth ions increases, the effect of photocatalytic degradation is lower than that of Example 2.
[0063] It can be seen from Examples 1 to 6 that the present invention adjusts the composite ratio of zinc oxide and the required ratio of ytterbium ions and erbium ions, zinc oxide provides more reactive sites for titanium dioxide, increases the specific surface area and light absorption of titanium dioxide, and effectively reduces the energy band width. At the same time, the doping of Yb also improves the light absorption to a certain extent, provides the utilization efficiency of visible light, and thus improves its photocatalytic reaction activity. During the experiment, it was found that in Example 1, when the molar ratio of rare earth ions Er to Ti was 1%, the molar ratio of rare earth ions Yb to Ti was 1%, and the molar ratio of Zn to Ti was 0.5%, the effect of improving the photocatalytic activity was most significant.
[0064] The above description of the embodiments is to facilitate the understanding and application of the present application by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these examples and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.
Claims
1. A rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst, characterized in that: The composite photocatalyst is obtained by combining zinc oxide with titanium dioxide and then doped with rare earth Yb 3+ and Er 3+ , rare earth Yb 3+ and Er 3+ The ratio of Zn to Ti needs to be configured; n(Zn):n(Ti)=5%, 10%, 15%, Er 3+ The doping ratio of Yb is fixed at n(Er):n(Ti)=1%, 2.5%, 5%; 3+ They are n(Yb):n(Ti)=1%, 2.5% and 5% respectively.
2. The rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%.
3. The rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1%.
4. The rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 0.5%.
5. The preparation process of the titanium dioxide composite material according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 0.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
6. The rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
7. The rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to claim 1, characterized in that: The molar ratio of Zn to Ti is 5%, the molar ratio of rare earth ion Er to Ti is 1.5%, and the molar ratio of rare earth ion Yb to Ti is 1.5%.
8. A method for preparing the rare earth ytterbium and erbium co-doped titanium dioxide-zinc oxide composite photocatalyst according to any one of claims 1 to 7, characterized in that: The steps include: (1) First, weigh 7 mL of tetrabutyl titanate and add it to 25 mL of anhydrous ethanol solution; stir the mixed solution of the two by magnetic stirring; (2) Accurately weigh a certain amount of ytterbium nitrate and erbium nitrate, put them into a beaker, add anhydrous ethanol and glacial acetic acid into a volumetric flask; stir the mixed solution magnetically; (3) slowly adding the mixed solution (2) into the mixed solution (1), stirring with a magnetic stirrer until a transparent sol is obtained; (4) standing at room temperature for aging, and then moving to a drying oven to dry into a xerogel; (5) Grinding the dry gel, transferring it to a crucible, and placing it in a muffle furnace for calcination. When it cools to room temperature, taking out the product; washing the product by centrifugation (using deionized water and ethanol to wash the product respectively); (6) Add an appropriate amount of zinc acetate to 10 mL of anhydrous ethanol and stir evenly; (7) taking out an appropriate amount of the particles in (5), adding them to (6), stirring and impregnating, and then centrifuging; (8) The solid powder obtained in (7) is dried, and then calcined in a muffle furnace. When the solid powder is cooled to room temperature, the product is taken out.
9. The preparation method according to claim 8, characterized in that: The YbN3O9·5H2O solution in step (2) is 0.1 mol / L, the Er(NO3)3·5H2O solution is 0.1 mol / L, and the C4H6O4Zn·2H2O solution in step (8) is 0.2 mol / L.
10. The preparation method according to claim 8, characterized in that: The magnetic stirring time in step (2) is 10 min; The volumetric flask in step (3) has a size of 100 ml; The magnetic stirring time in step (3) is 30 min; The stirring time of step (5) is 30 min; The drying oven temperature in step (7) should be set to 90°C for 6 hours; The muffle furnace calcination temperature in step (8) is 500° C. and the calcination time is 2 h.
Citation Information
Patent Citations
Preparation method of double-rare earth co-doped nanometer titanium dioxide photocatalyst
CN102059110A
Preparation method of double rare earth co-doped titanium dioxide catalyst for treatment of tetracycline wastewater
CN107376891A